Experimental study and numerical simulation of replaceable corrugated steel plate-concrete composite shear walls. Issue 127 (December 2019) - Wang, Wei; Song, Jiangliang; Hou, Mingyue; Liu, Gewei; Wang, Wanzhi
Abstract: In this paper, a new structural form of installing a replaceable corner tension-and-compression damper (RCTCD) at the bottom of corrugated steel plate-concrete (CSPC) shear walls was proposed. This new structural wall is called a replaceable corrugated steel plate-concrete (RCSPC) composite shear wall. After a strong earthquake, the damage is mainly concentrated in the RCTCDs, and the function of the structure is quickly restored by replacing the RCTCDs. To study the seismic performance of RCSPC shear walls, cyclic loading tests on one replaceable horizontally corrugated steel plate-concrete (RHCSPC) composite shear wall and one replaceable vertically corrugated steel plate-concrete (RVCSPC) composite shear wall were conducted. To verify the feasibility of replacement, both the RHCSPC and the RVCSPC structural walls experienced replacement and reloading processes. The test results indicate that the structural behaviour of the two structural walls were flexure dominant. The damage in the RCSPC structural walls were mainly concentrated in the RCTCDs. The replacement of the RCTCDs can be implemented conveniently after residual deformation occurs in the structure. Compared with the RHCSPC structural wall, the RVCSPC structural wall had better seismic performance. Subsequently, the experimental and numerical simulation results were compared, the numerical simulation could predict the shear strength of the RVCSPC and RHCSPC shear walls with good accuracy. In addition, simplified formulas were proposed to evaluate the shear buckling strength of the RVCSPC and RHCSPC shear walls. The calculated results agree well with the test results, verifying the accuracy of the proposed formula. Highlights: An innovative use of installing the damper at the toe of the CSPC shear walls is proposed. A new kind of replaceable corner tension-compression dampers (RCTCDs) at the bottom of the shear walls is designed. The seismic performance of the RCSPC shear walls that include ductility, energy dissipation and so on are analysed. The feasibility of replacing the RCTCDs in the RCSPC shear walls is discussed. Simplify formulas are proposed to evaluate the shear buckling strength of the RCSPC shear walls.